MADRASAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM DALAM KETAHANAN NASIONAL IPOLEKSOSBUDHANKAM UNTUK MEWUJUDKAN KEHIDUPAN BERBANGSA DAN BERNEGARA - Fitri, H. Aidil; Hatta, M. (MAJALAH ILMIAH WIDYA, 2012)
Madrasah is a community-based education to provide education based on the distinctiveness of religious, social, culture,aspirations, and educational potential of the community as a manifestation of, by, and for the community. The purpose of this paperto discuss the role of madrasahs as an educational institution in the national security ideology of Islamic socio-cultural politics ofdefense and security to realize the life of the nation. The method used is based on library research. It can be concluded that all thepeople of Indonesia must have education and teaching to the intellectual life of the nation.